The effect of using natural adhesive from manihot esculenta (cassava) starch on the physico-mechanical properties of papercrete - Molinos, Jotham Norman P.; Cartajenas, Ken Alexis S. (2017)
Waste is a global issue if not properly dealt with and poses a threat to public health and the environment. Recycling saves energy, reduces raw material extraction, and is beneficial for the environment. A relatively new building material called Papercrete uses waste paper, cement and water. This material can be an alternative to concrete. Additives can be added to Papercrete to improve its behavior under compressive load. Ancient builders used natural adhesives/mortars to build walls and structure such as cassava starch. This study aimed to find out the effect of cassava starch adhesive on the properties of Papercrete as an environment- friendly alternative material in building construction. It also specifically identified how the Papercrete samples with different volumes (4%, 6%, 8%, and 10%) of cassava starch differ in terms of weight, compressive strength, water absorptivity and flammability. After 28 days of curing, the sample with 10% (by cement weight)cassava starch adhesive weighed the lightest. The sample with the highest water resistance had 8% cassava starch adhesive and the sample with the highest compressive strength had 4% cassava starch adhesive. All of the samples were incombustible on a one-hour fire resistance test. With this result at hand, papercrete with cassava starch adhesive can be used for indoor purposes such as interior walls not exposed to water
Thesis (BS Architecture) -- University of the Philippines Mindanao, June 2017